PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN SISWA KELAS XII PADA MADRASAH ALIYAH NEGERI 1 PEKANBARU - rupat, herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2020)
This study aims to determine the Effect of Service Quality on Class XII Student Satisfaction in Pekanbaru 1 State Madrasah Aliyah. The variables in this study consisted of dependent (service quality) and independent (student satisfaction) variables, while the population in this study was 354 students and then simplified by using the Slovin formula so that a sample of 78 students was obtained, using the accidental sampling technique. Data analysis in this study uses quantitative descriptive analysis while to test the feasibility of the data collected instrument testing, validity test, reliability test, simple linear regression test, t test and coefficient determination. The results of the study found a simple linear regression equation model Y = 20,626 + 0,715X, based on the data in the t test where tcount is greater than t table 6.241> 1.99167 means there is a significant influence between service quality on student satisfaction. And the results of the determination coefficient test of 0.339 (33.9%) while the remaining 66.1% is influenced by other variables that are outside of this service quality variable.